MOTIVASI KERJA PEGAWAI DINAS PARIWISATA SENI DAN BUDAYA KABUPATEN KARIMUN - Anggriani, Gita; Achnes, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Motivation is very important in an organization . in developinh the organization, people only focus on how the results of the efforts that have been made, so that the management of human resources within the organization less attention. With their work motivation of the employes then any work performed will be easier. The research uses descriptive quantitative method forissues raised. The sample in this study were 34 respondents, taken using probabilility sampling. While the data collection techniques in this study using observation, questionnaires, interview, and documentation. Using a likert scale as a measure to determine the length of the short interval.whit sub varianles that exist on work motivation is divide into : the statisfaction factor and maintenance factor. The results of research conducted in the field with their research on employee motivation department of tourism and culturan district karimun, with the theory of motivation is divide into two sub variables, factor gratification and maintenance factor, the results obtained in the field, namely regarding work motivation